2018
DOI: 10.2217/bmm-2018-0015
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Biomarkers for Lung Cancer Progression

Abstract: A comparative analysis was also carried out on related transcriptomic datasets, which indicates that the proposed biomarkers provide discerning power for accurate stage prediction, and will be improved when larger-scale proteomic quantitative technologies become available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…However, about 20.00% of stage I patients undergone radical resection still have local recurrence or distant metastasis (3). Though much effort has been reported in searching for biomarkers that aid in predicting the prognosis of patients with early lung adenocarcinomas (4,5), tumor size is still an irreplaceable prognostic factor, especially in the newly published 8 th edition of the American Joint Committee on Cancer (AJCC) Staging Manual lung cancer staging system, which emphasizes much more on each centimeter increase in tumor size (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…However, about 20.00% of stage I patients undergone radical resection still have local recurrence or distant metastasis (3). Though much effort has been reported in searching for biomarkers that aid in predicting the prognosis of patients with early lung adenocarcinomas (4,5), tumor size is still an irreplaceable prognostic factor, especially in the newly published 8 th edition of the American Joint Committee on Cancer (AJCC) Staging Manual lung cancer staging system, which emphasizes much more on each centimeter increase in tumor size (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…However, despite advances in the diagnosis and treatment of LUAD, the OS time of patients with LUAD remains poor (29). Recent studies have identified molecular biomarkers throughout the various clinical stages and pathological tissue types (30,31). However, patients with the same clinical and pathological features at diagnosis often have a completely different final prognoses (32).…”
Section: Discussionmentioning
confidence: 99%
“…[2] Lung adenocarcinoma (LUAD) is the main subtype of NSCLC and accounts for two-thirds of all lung cancer patients. [3,4] No obvious clinical symptoms in the early stage cause a considerable proportion of LUAD patients to be diagnosed at an advanced stage. [5] Hence, the best therapeutic strategy is to seek effective markers for early diagnosis and treatment of LUAD.…”
Section: Introductionmentioning
confidence: 99%